Analisis Perilaku Pengunjung dalam Membuang Sampah di Area Taman Suropati - Neca Purnama Sari; Suesilowati; Rosandi Ardi Noegraha (Bulletin of Community Engagement, 2024)
Sustainable cities focus heavily on people's quality of life. The city park perspective is an important factor that makes us livable, pleasant and attractive for city residents. There are still problems in maintaining city parks in the social and environmental aspects that support sustainable city parks. This problem is exacerbated by the behavior of many visitors who do not pay attention to the cleanliness of the city park environment, so that the anticipated green open space does not match reality, there is a lot of rubbish strewn about, and the smell of rubbish, giving rise to comfort and health problems. The aim of this research is to determine visitor behavior, seen from cultural, social, personal and psychological aspects. Based on the results of this research, city parks provide information about visitor behavior regarding awareness of throwing rubbish in the places provided. If city parks are well kept clean and their quality improves, it is not impossible that city parks will truly be beneficial for urban communities.